1993
DOI: 10.1056/nejm199303253281204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stimulus Intensity and Electrode Placement on the Efficacy and Cognitive Effects of Electroconvulsive Therapy

Abstract: Increasing the electrical dosage increases the efficacy of right unilateral electroconvulsive therapy, although not to the level of bilateral therapy. High electrical dosage is associated with a more rapid response, and unilateral treatment is associated with less severe cognitive side effects after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
447
3
25

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 855 publications
(496 citation statements)
references
References 26 publications
21
447
3
25
Order By: Relevance
“…While we agree with most of their findings, we would like to add an important interpretation of their results, as it relates to clinical practice: while the group data suggest an equivalent overall antidepressant efficacy rate for the two techniques, at the individual patient level, the approximately half of all patients who do not remit with right unilateral electrode placement should be crossed over to bilateral (Sackeim et al 1993. While the randomized trial data for this assertion are few, crossover to bilateral electrode placement is a nearly ubiquitous clinical practice that has been employed successfully for many thousands of patients worldwide (Lapidus & Kellner, 2011).…”
supporting
confidence: 75%
“…While we agree with most of their findings, we would like to add an important interpretation of their results, as it relates to clinical practice: while the group data suggest an equivalent overall antidepressant efficacy rate for the two techniques, at the individual patient level, the approximately half of all patients who do not remit with right unilateral electrode placement should be crossed over to bilateral (Sackeim et al 1993. While the randomized trial data for this assertion are few, crossover to bilateral electrode placement is a nearly ubiquitous clinical practice that has been employed successfully for many thousands of patients worldwide (Lapidus & Kellner, 2011).…”
supporting
confidence: 75%
“…A description of the battery and the derived outcome measures are presented in Table 1. The modified MiniMental State exam (mMMS) (Stern et al, 1987), a measure of global cognitive status and an expanded version (range 0-57) of the original MMS (Folstein et al, 1975), has shown sensitivity to variation in ECT technique (Sackeim et al, 1993. Psychomotor function was assessed with three measures of reaction time (RT): Simple (SRT) (Benton, 1977), Choice (CRT) (Benton and Blackburn, 1957), and Stroop RT (MacLeod, 1991).…”
Section: Study Measuresmentioning
confidence: 99%
“…Randomized-controlled trials have shown more severe short-term memory deficits with sine wave compared to brief pulse stimulation (Valentine et al, 1968;Weiner et al, 1986), bilateral (BL) compared to right unilateral (RUL) electrode placement (Lancaster et al, 1958;Sackeim et al, 1986;Sackeim et al, 1993;Sackeim et al, 2000), and higher electrical dosage (McCall et al, 2000;Ottosson, 1960;Sackeim et al, 1993). These adverse effects are reduced by the use of RUL ECT with brief or ultrabrief pulse stimulation and electrical dosage titrated to the needs of the individual patient (Sackeim, 2004b).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to functional imaging studies of conventional antidepressant medications, pramipexole did not alter metabolism in the amygdala but did increase activity in the premotor cortex, hippocampus, posterior cingulate cortex, and superior temporal gyrus. 112 For electroconvulsive therapy (ECT), the most effective acute depression treatment to date, good clinical response is associated with electrode placement over the PFC 113 and with relatively decreased activity after treatment in the PFC, anterior cingulate, and temporal and parietal cortices. 39,114 Cognitive behavioral therapy (CBT) and interpersonal therapy (IPT), two forms of psychotherapy studied for efficacy in the treatment of depression, have effects on affective circuitry that are distinct from those of antidepressant medication.…”
Section: Presumptive Mood Disorder Circuitsmentioning
confidence: 99%